2021
DOI: 10.3390/ijms22052518
|View full text |Cite
|
Sign up to set email alerts
|

Selenite Inhibits Notch Signaling in Cells and Mice

Abstract: Selenium is an essential micronutrient with a wide range of biological effects in mammals. The inorganic form of selenium, selenite, is supplemented to relieve individuals with selenium deficiency and to alleviate associated symptoms. Additionally, physiological and supranutritional selenite have shown selectively higher affinity and toxicity towards cancer cells, highlighting their potential to serve as chemotherapeutic agents or adjuvants. At varying doses, selenite extensively regulates cellular signaling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…These studies have shown that, at supra-nutritional concentrations, MSC and SLM exhibit anti-angiogenic and anti-cancer effects. The well-studied inorganic selenium compound selenite ( Figure 2 ) is clinically utilized and supplemented in the diet of patients with the endemic Keshan disease [ 61 , 62 ]. Keshan disease arises due to insufficient dietary selenium levels, which can result in cardiovascular atrophy if not properly addressed [ 61 , 62 ].…”
Section: Regulation Of Signaling Pathways By Selenium In Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…These studies have shown that, at supra-nutritional concentrations, MSC and SLM exhibit anti-angiogenic and anti-cancer effects. The well-studied inorganic selenium compound selenite ( Figure 2 ) is clinically utilized and supplemented in the diet of patients with the endemic Keshan disease [ 61 , 62 ]. Keshan disease arises due to insufficient dietary selenium levels, which can result in cardiovascular atrophy if not properly addressed [ 61 , 62 ].…”
Section: Regulation Of Signaling Pathways By Selenium In Cancermentioning
confidence: 99%
“…The well-studied inorganic selenium compound selenite ( Figure 2 ) is clinically utilized and supplemented in the diet of patients with the endemic Keshan disease [ 61 , 62 ]. Keshan disease arises due to insufficient dietary selenium levels, which can result in cardiovascular atrophy if not properly addressed [ 61 , 62 ]. The supplementation of selenite into the diet successfully treats Keshan disease and the associated symptoms, suggesting the therapeutic benefits that can be imparted by selenite [ 61 , 62 ].…”
Section: Regulation Of Signaling Pathways By Selenium In Cancermentioning
confidence: 99%
See 3 more Smart Citations